Serum magnesium level in the first trimester of pregnancy as a predictor of pre-eclampsia - a pilot study - Velibor Čabarkapa; Mirjana Bogavac; Ana Jakovljević; Lato Pezo; Aleksandra Nikolić; Zoran Belopavlović; Djerić Mirjana (Taylor & Francis Group, 2018)
Objectives: The aim of this study was to evaluate the importance of serum concentration of magnesium (Mg) in the first trimester of pregnancy for predicting pre-eclampsia (PE). Methods: This prospective study included 403 pregnant women over 18, with singleton pregnancy (from 11 to 14 weeks of pregnancy). The subjects were divided into a group who subsequently developed PE (PEKT) (n = 61), and a group of healthy pregnancies with no complications and with normal outcomes (TNT) (n = 342). In the first trimester, urea, creatinine, uric acid, Mg, free beta subunit of human chorionic gonadotrophin, plasma protein A related to pregnancy, and C-reactive protein were determined. We followed all subjects until the end of pregnancy. Results: Serum Mg is significantly lower in PEKT than in TNT group (p < 0.001). The serum first trimester Mg level cutoff at ≤0.81 mmol/L had a sensitivity of 77.0% and specificity of 71.6% for the detection of women with PEKT. The level of serum Mg has the strongest significant positive correlation (p < 0.05) with the week of gestational outcomes (R = 0.442), weight (R = 0.416), and Apgar score (R = 0.343) of the newborns, and the strongest significant negative correlation with the number of miscarriages (R = −0.413), serum creatinine (R = −0.471), and the number of pregnancies (R = −0.326). The week of gestational outcome is predicted with the greatest reliability by the serum Mg. Conclusions: Serum Mg level during the first trimester of pregnancy is a significant prediction tool for PE and could also play an important role in predicting the week of gestational outcome and birth weight of newborns.